Diversity of Antisense and Other Non-Coding RNAs in Archaea Revealed by Comparative Small RNA Sequencing in Four Pyrobaculum Species - Bernick, David L.; Dennis, Patrick P.; Lui, Lauren M.; Lowe, Todd M. (Frontiers in Microbiology, 2012)
A great diversity of small, non-coding RNA molecules with roles in gene regulation and RNA processing have been intensely studied in eukaryotic and bacterial model organisms, yet our knowledge of possible parallel roles for small RNAs in archaea is limited. We employed RNA-seq to identify novel small RNA across multiple species of the hyperthermophilic genus Pyrobaculum, known for unusual RNA gene characteristics. By comparing transcriptional data collected in parallel among four species, we were able to identify conserved RNA genes fitting into known and novel families. Among our findings, we highlight three novel cis-antisense small RNAs encoded opposite to key regulatory (ferric uptake regulator), metabolic (triose-phosphate isomerase), and core transcriptional apparatus genes (transcription factor B). We also found a large increase in the number of conserved C/D box small RNA genes over what had been previously recognized; many of these genes are encoded antisense to protein coding genes. The conserved opposition to orthologous genes across the Pyrobaculum genus suggests similarities to other cis-antisense regulatory systems. Furthermore, the genus-specific nature of these small RNAs indicates they are relatively recent, stable adaptations.